Strategi Komunikasi Penyiar Radio Sushi 99.1 Fm Dalam Mempertahankan Program Unggulan Pantun Balega Kepada Pendengar Loyal Di Kota Padang - Fareza, Rahmat; Flowerina, Indria (CV. ITTC INDONESIA, 2024)
In the era of communication 5.0, technology is developing rapidly, causing radio to be less attractive to the younger generation. However, Radio Sushi FM, with the program